2016
DOI: 10.1021/acs.nanolett.6b02815
|View full text |Cite
|
Sign up to set email alerts
|

Negative Thermophoresis in Concentric Carbon Nanotube Nanodevices

Abstract: Positive and negative thermophoresis in fluids has found widespread applications from mass transport to molecule manipulation. In solids, although positive thermophoresis has been recently discovered in both theoretical and experimental studies, negative thermophoresis has never been reported. Here we reveal via molecular dynamics simulations that negative thermophoresis does exist in solids. We consider the motion of a single walled carbon nanotube nested inside of two separate outer tubes held at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…This was later confirmed by a scanning electron microscopy experiment [6]. MD remains the state-of-the-art method to explore molecular transport at nanoscale numerically [9,17].…”
Section: Introductionmentioning
confidence: 87%
“…This was later confirmed by a scanning electron microscopy experiment [6]. MD remains the state-of-the-art method to explore molecular transport at nanoscale numerically [9,17].…”
Section: Introductionmentioning
confidence: 87%
“…Six years later, carbon nanotubes (CNTs) were pioneered by Sumio Iijima [2]. One-dimensional (1D) materials have historically been one of the most extensively studied classes of materials due to their diverse physical and chemical properties [3][4][5][6][7][8][9][10][11][12][13][14]. The breakthrough of single-layer graphene [15], initialized by Konstantin Novoselov and Andre Geim in 2004, has triggered exceptional interest in two-dimensional (2D) materials in the form of a single-atom-thick or polyhedral-thick layer with either covalent or ionic bonding in the plane and van der Waals bonding out of plane [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is to date a lack of knowledge of the anisotropic thermal properties of MWCNTs, despite its significant importance in developing nanoscale thermal devices. 23 Based on molecular dynamics (MD) simulations, here we investigate the thermal conducting properties of double-walled carbon nanotubes (DWCNTs). It is found that DWCNTs may have an extremely high anisotropic thermal conductivity ratio, 5 times higher than that of bilayer graphene sheet and two orders higher than that of graphite, indicating DWCNTs can be a tremendously important thermal management materials for high performance applications.…”
Section: Introductionmentioning
confidence: 99%